Los distintos soportes de la represión en América Latina: una mirada sobre los archivos de las fuerzas de seguridad del Estado - Marengo, María Eugenia (2014)
The archives of the state security forces in Latin America, were formed as fundamental elements for the repression, control and surveillance of different political actors and subjects of the civil society along the twentieth century. Through the following pages are intended to describe the origins and practices now redefine these files. The purpose of this work focuses on making visible the different files executed by the control agencies in some countries in Latin America, particularly the cases of the Historical Archive of the National Police of Guatemala (1882-1997) and the Central Division of Documentation, record and Archive, the Intelligence Directorate of Police of the Province of Buenos Aires, Argentina (1956 - 1998).